SnoezelenCAVE: Virtual reality CAVE Snoezelen framework for Autism spectrum disorders - Perhakaran G.; Yusof A.M.; Rusli M.E.; Yusoff M.Z.M.; Mahidin E.M.M.; Mahalil I.; Zainuddin A.R.R. (Springer Verlag, 2023)
Caves; Diseases; Information science; Autism spectrum disorders; Hand motion; Immersive virtual reality; Interaction methods; Multi-Sensory; Snoezelen; Visual learning; Voice-recognition systems; Virtual reality